Political Economy of Communication Conferences in Indonesia - Masduki Masduki (Komunikator, 2022)
This study was triggered by the widespread scietific conferences in the field of communication during the past six years, from 2015-2021 in Indonesia. It intends to find a model of an academic conference within the trend of liberalizing universities. In addition to identifying its technical aspects (themes, speakers, funding, types of organizers, and post-conference publication choices), this study examines the macro-political aspects of organizing scientific conferences. This study uses a qualitative method. The author observed 36 conference posters from 2015 to 2021 and conducted field visits and interviews with selected conference organizers. The author also examines government policy documents directly and indirectly related to those scientific conferences in Indonesia. The study found a massive growth in the academic conferences, with various organizers (universities, associations of academia, etc.). It follows the trend of academic mobility, knowledge exchange, and collaboration which are driven by the ‘commodification of knowledge’. Amidst the lack of conference regulation, it tends to follow ’the logic of market competition’, not complying with the mission ofacademic dissemination itself. Most conferences placed bureaucrats more privileged above scientists, offering additional activities such as city tours or non-academic events showing academia’s dependence on political paternalism and economic power.